DIGITAL TECHNOLOGIES IN CHEMISTRY TEACHER TRAINING: THEORETICAL AND METHODOLOGICAL ANALYSIS - Olena Kochubei (Неперервна професійна освіта: теорія та практика)
The article substantiates the theoretical and methodological foundations for the integration of digital educational technologies into the professional training of future chemistry teachers, focusing on the teaching of inorganic chemistry. The relevance of the study is determined by the need to update the content and methods of teaching chemistry in accordance with current trends in the digitalization of education. Inorganic chemistry, as a fundamental component of professional training, requires the use of tools capable of visualizing complex concepts, modeling chemical processes, and supporting research activities. The study presents a logical and content-based analysis of digital educational resources, their classification by functional characteristics, and the pedagogical conditions necessary for their effective application. Five types of digital tools have been identified: informational and representational, modeling, research and experimental, evaluative and reflective, and project-based constructive. The appropriateness of each group of resources is determined by the content of specific topics and didactic goals. The article outlines conditions for the successful integration of digital technologies in the training process: incorporation into curricula, availability of methodological support, digital competence of lecturers, and access to technological infrastructure. International experience in the integration of digital didactics is discussed as a reference point. The results of the study can be used to develop digital learning scenarios and didactic solutions in the field of inorganic chemistry.